2021
DOI: 10.3390/biom11060887
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolic Extracts of Adlay Testa and Hull and Their Active Biomolecules Exert Relaxing Effect on Uterine Muscle Contraction through Blocking Extracellular Calcium Influx in Ex Vivo and In Vivo Studies

Abstract: Dysmenorrhea is one of the most prevalent disorders in gynecology. Historically, adlay (Coix lachryma-jobi L. var. Ma-yuen Stapf.) has been explored for its anti-tumor, pain relief, anti-inflammatory, and analgesic effects. The aim of this study was to evaluate the effects of adlay seeds on the inhibition of uterine contraction and thus dysmenorrhea relief, in vitro and in vivo. HPLC-MS and GC were used to elucidate the ethyl acetate fraction of adlay testa ethanolic extract (ATE-EA) and ethyl acetate fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…As mentioned above, many metabolites are relevant to mitochondrial function, so it can be speculated that mitochondria are an important target in PD research. Studies also showed that intracellular calcium was significantly increased in uterine smooth muscles after oxytocin stimulation [ 67 , 68 ]. Endoplasmic reticulum membrane is essential for intracellular calcium homeostasis, and here, it might contribute to PD development through regulating intracellular calcium [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, many metabolites are relevant to mitochondrial function, so it can be speculated that mitochondria are an important target in PD research. Studies also showed that intracellular calcium was significantly increased in uterine smooth muscles after oxytocin stimulation [ 67 , 68 ]. Endoplasmic reticulum membrane is essential for intracellular calcium homeostasis, and here, it might contribute to PD development through regulating intracellular calcium [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…These four parts extracted using ethanol to obtain Coix husk ethanol extract (AHE), Coix seed coat e extract (ATE), Coix bran ethanol extract (ABE) and polished Coix seed ethanol (PAE). These four ethanol extracts are then divided into the n-hexane layer (He acetate layer (Ea), n-butanol layer (Bu) and water layer (Wa) using solvents of d polarities [12]. Following the use of the MTT analysis method to explore the antip ative effects of these test samples at different concentrations (0, 12.5, 25, 50 and 100 μ on breast cancer cells (MCF-7) and cervical cancer cells (HeLa) for 72 h, the res vealed that the most effective subfractions were those extracted from AHE and AT previous study, the treatment of blood cancer cells HL-60 and U937 with a metha tract of Coix shell (AHM) for 72 h significantly inhibited cell growth with IC50 va 70 and 61 μg/mL, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Coix has been among the first-class materials used as medicinal and dietary supplements since ancient times. Recent studies have also pointed out that Coix has antitumor [8], anti-allergic [9], hypolipidemic [10], hypoglycemic [11], anti-oxidant [12] and ovulation-inducing effects [13].…”
Section: Introductionmentioning
confidence: 99%
“…Adlay seed coixol has an analgesic effect [ 6 ]. Adlay seeds (flavonoids, phytosterols, and fatty acids) can inhibit uterine contractions and relieve dysmenorrhea in vitro and in vivo [ 113 ]. Adlay has been used as therapeutic agent for dysmenorrhea as its naringenin and quercetin inhibit PGF 2α -induced uterine contractions and inhibited uterine contraction by blocking external Ca 2+ influx, leading to a decrease in the intracellular Ca 2+ concentration [ 114 ].…”
Section: Action Pathway Against Disease Of Adlaymentioning
confidence: 99%
“…Adlay and its extracts are rich in 30 ingredients with more than 20 health effects. The effect of adlay on human health has been confirmed by PubMed and Google search, including its anti-cancer [ 46 , 167 ], anti-inflammation [ 97 ], anti-obesity [ 11 , 12 , 97 ], liver protection [ 140 ], anti-virus [ 8 , 105 , 106 ], cardiovascular protection [ 11 ], anti-hypertension [ 11 , 108 ], heart disease prevention [ 11 , 70 ], endocrine regulation [ 75 ], anti-diabetes [ 132 ], osteoporosis prevention [ 12 ], and analgesic effects [ 113 ].…”
Section: The Food and Pharmaceutical Industrymentioning
confidence: 99%